Perilaku Perundungan di Dunia Maya Siswa Ditinjau dari Kualitas Kelekatan Teman Sebaya dan Kontrol Diri: Cyberbullying Behavior Reviewed from Peer Attachment Quality and Self Control - Putri Swasti Rasmita Rukmi; Lisnawati, Lisnawati (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2020)
Cyberbullying has been found massively among teenagers recently. There are two factors related cyberbullying, internal and external factors. Peer attachment as the external factor and self-control as the internal factor have been recognized as the factors of cyberbullying. Both of these variables correlated with cyberbullying. This research aims to examine the relationship between the quality of peer attachment and self-control to cyberbullying among senior high school’s student in Ponorogo. This is a quantitative research using cyberbullying scale, quality peer attachment scale and self-control scale. There are 81 students included as the sample study. The result of multiple regression analysis shows that the quality of peer attachment and self-control have no correlations with cyberbullying. It is also acknowledged that the cyberbullying is only affected by one predictor (r=0.304, p=0.006). Although the major hypothesis in this study is rejected, the self-control variable is known having significant negative correlation to cyberbullying.